Partial functional correspondence - Rodolà,E; Cosmo,L; Bronstein,MM; Torsello,A; Cremers,D (Computer Graphics Forum: the international journal of the Eurographics Association, 2017)
In this paper, we propose a method for computing partial functional correspondence between nonrigid shapes. We use perturbation analysis to show how removal of shape parts changes the Laplace–Beltrami eigenfunctions, and exploit it as a prior on the spectral representation of the correspondence. Corresponding parts are optimization variables in our problem and are used to weight the functional correspondence; we are looking for the largest and most regular (in the Mumford–Shah sense) parts that minimize correspondence distortion. We show that our approach can cope with very challenging correspondence settings.